1988
DOI: 10.2118/14045-pa
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Upstream Differencing

Abstract: Summary. A complete convergence analysis is carried out for upstream differencing as applied to one-dimensional (1D) tilted reservoirs experiencing gravity-segregation effects and possible countercurrent flows. It is shown that the standard upstream method converges to the correct physical solution of this problem, provided that an appropriate stability physical solution of this problem, provided that an appropriate stability condition holds. Results from the theory of monotone-difference sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 7 publications
0
42
0
Order By: Relevance
“…This assumption is quite common and realistic when considering immiscible problems [6,9,28,34] but breaks down for some miscible and thermal models. This assumption is not necessary (see "Appendix 2"), but is useful since it simplifies the initial presentation of the scheme while retaining the fundamental nature of the scheme.…”
Section: Discretization Of the Saturation-dependent Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is quite common and realistic when considering immiscible problems [6,9,28,34] but breaks down for some miscible and thermal models. This assumption is not necessary (see "Appendix 2"), but is useful since it simplifies the initial presentation of the scheme while retaining the fundamental nature of the scheme.…”
Section: Discretization Of the Saturation-dependent Propertiesmentioning
confidence: 99%
“…An advantage of the phase-based approach is that stationary points, i.e., points in the hyperbolic flux function f (s) where f (s 0 ) = 0, which occur due to gravity, need not be identified and handled specially. SPU has been shown to be monotone for multiphase flows under physically reasonable conditions on the flux function [9,28,34] and behaves similar to Godonuv's method, although it is somewhat more diffusive for countercurrent flows [9,37]. In multi-D, SPU is generally applied in a dimension-by-dimension manner, though some multi-D [15,18,36] and highorder schemes [7,10,15,19] have been proposed in the finite volume context.…”
Section: Introductionmentioning
confidence: 99%
“…This type of a condition was explicitly written out in [25] for the case of one rock type, and a slight modification of it gives the result in our case. Then, we can prove in a straightforward manner.…”
Section: Lemma 53 the Interface Flux F As Defined In Eq 47mentioning
confidence: 99%
“…In particular, for equations governing two-phase flow in porous media, the numerical scheme that is commonly used by petroleum engineers is the upstream mobility flux scheme (see [7,9,20,25]). An alternative finite difference (volume) method of the Godunov type based on exact solutions of the Riemann problem was presented in Adimurthi et al [2].…”
mentioning
confidence: 99%
“…Sammon [42] showed that upstream weighting for a two-phase Buckley-Leverett problem is an E-scheme, provided that sufficiently small timesteps are used. In other words, the largest stable timestep for the upstream weighting method is smaller than the CFL timestep.…”
mentioning
confidence: 99%